The family in Late Antiquity : the Rise of Christianity and the Endurance of Tradition - Nathan, Geoffrey S.. (London Routledge, 2012)
Comprehensive study of the family in the later Roman Empire, from approximately 300 AD to 550 AD. Geoffrey Nathan analyses the classical Roman family as well as early Christian notions of this most basic unit of social organisation. Using these models as a contextual backdrop, he then explores marriage, children, domestic servitude, and other familial institutions in late antiquity. He brings together a diverse collection of sources, transcending traditional studies that have centred on the legal record. [Routledge]